Naphthyridine Derivatives Induce Programmed Cell Death in Naegleria fowleri - Aitor Rizo-Liendo; Iñigo Arberas-Jiménez; Endika Martin-Encinas; Ines Sifaoui; María Reyes-Batlle; Javier Chao-Pellicer; Concepción Alonso; Francisco Palacios; José E. Piñero; Jacob Lorenzo-Morales (Pharmaceuticals, 2021)
Primary amoebic encephalitis (PAM) caused by the opportunistic pathogen Naegleria fowleri is characterized as a rapid and lethal infection of the brain which ends in the death of the patient in more than 90% of the reported cases. This amoeba thrives in warm water bodies and causes infection after individuals perform risky activities such as splashing or diving, mostly in non-treated water bodies such as lakes and ponds. Moreover, the infection progresses very fast and no fully effective molecules have currently been found to treat PAM. In this study, naphthyridines fused with chromenes or chromenones previously synthetized by the group were tested in vitro against the trophozoite stage of two strains of N. fowleri. In addition, the most active molecule was evaluated in order to check the induction of programmed cell death (PCD) in the treated amoebae. Compound 3 showed good anti-Naegleria activity (61.45 ± 5.27 and 76.61 ± 10.84 µM, respectively) against the two different strains (ATCC® 30808 and ATCC® 30215) and a good selectivity compared to the cytotoxicity values (>300 µM). In addition, it was able to induce PCD, causing DNA condensation, damage at the cellular membrane, reduction in mitochondrial membrane potential and ATP levels, and ROS generation. Hence, naphthyridines fused with chromenes or chromenones could be potential therapeutic agents against PAM in the near future.